A scaleable approach to emissions-innovation record linkage - Mark Huberty; Amma Serwaah; Georg Zachmann (Bruegel, 2014)
This paper reports an approach to linking data on European emitters to data on their innovation practices. We illustrate a straightforward approach to record linkage between the European Union Community Integrated Transaction Log (CITL) and the PATSTAT international patent database. We show how that record linkage can be maintained with relatively minimal human input.
Keywords: 330